How beans are beating hunger in Burundi - Pan-Africa Bean Research Alliance (Pan-Africa Bean Research Alliance, 2020)
Burundi’s population has been expanding far faster than its economy. And while the agriculture sector contributes around 40% of GDP and to over 95% of food supplies, high pressure on land is leading to soil fertility depletion, eroding the country’s capacity to ramp up food production for a growing population. The Flagship project: “Improving food security, nutrition, incomes, natural resource base and gender equity for better livelihoods of smallholder households in sub-Saharan Africa” between 2015 and 2020, sought to boost bean production and yields as a staple crop. Already an important food crop in the country, beans provide 50% of daily protein and 20% of calories. Improved bean varieties with high levels of iron and zinc also alleviate micronutrient deficiencies particularly in children and women. Beans also help farmers threatened by climate change to stagger food supply through harsher seasons, with edible leaves and pods allowing growers to sell or store dry beans. While bean volumes rank only after sweet potato and bananas in the country, lowyielding varieties were grown on around half of all land. Yields also declined during periods of political instability between 1993 and 2005. However, in recent years, yields have recovered in part due to efforts of the Pan-Africa Bean Research Alliance and partners, releasing 23 climate resilient highyielding, nutrient rich and farmer preferred varieties between 2015 and 2019.